Perception of Dentistry graduates in relation to professional training with emphasis on interprofessional education - Barros , Maria Cynésia Medeiros de; Menezes , Cláudia Callegaro de; Vianna , Ana Luiza Barboza; Prado , Fernanda da Silva (Seven Editora, 2024)
The objective of this chapter was to reflect on training in Dentistry, including the perception of undergraduate graduates in Dentistry in Rio de Janeiro about the quality of professional training with emphasis on interprofessional education. We present a study where an online questionnaire was applied to graduates of three Dentistry courses, two public institutions and one private, to students graduated between 2016.2 and 2019.1. The structured questionnaire used contained 41 questions to analyze the quality of the academic activities offered during the training of these professionals. The questions involved four dimensions: (1) profile of the graduate, (2) orientation of health care, (3) teaching-service integration, and (4) pedagogical approach. In this study, the answers to 9 questions from the four dimensions were presented. The results show that graduates of the Dentistry courses evaluated are satisfied with the quality of the professional training achieved through the academic activities offered by their courses. Especially those related to the formation of the professional profile and health promotion. However, the perception of the graduates indicates that multiprofessional/interprofessional experiences and living in the SUS still need to be improved, encouraging students to participate in internships and extension projects, thus training professionals capable of working in the SUS and in the existing social context. DOI:https://doi.org/10.56238/sevened2023.005-015